PATHOGENETIC SIGNIFICANCE OF OZONE THERAPY IN COMPLEX TREATMENT OF INFLAMMATORY DISEASES OF THE REPRODUCTIVE SYSTEM - Бубнова, Лидия Евгеньевна; Алексеева, Наталья Викторовна; Иванов, Леонид Николаевич; Павлова, Олимпиада Вячеславовна (Medicine in Kuzbass, 2024)
The purpose of the study – to evaluate changes in immune disorders, products of lipid peroxidation, factors of the coagulation and anticoagulation system of the blood in women with inflammatory diseases of the pelvic organs (IDPO).Research materials and methods. A comprehensive clinical and laboratory examination of 59 women aged 18 to 43 years was conducted. The first group included 33 patients who were prescribed complex etiotropic therapy with ozonized NaCl solution 0.9% – 400.0 ml intravenously. The second group included 26 patients who received prescribed therapy without ozone therapy.The results of the study and their discussion. By the end of the study, cellular and humoral immunity normalized in women of the first group. A significant decrease in intermediate products of lipid peroxidation was noted: malondialdehyde (MDA) decreased from 0.09 ± 0.01 to 0.04 ± 0.09 units ext. (by 44 %). The anticoagulant potential increased: the prothrombin index in the first group decreased by 10.3 % compared to the second group. Fibrinolytic activity (FA) in the first group decreased by 34 % than in the second.Conclusions. The effectiveness of the ozone therapy inclusion in the complex treatment of patients with IDPO is a reliable manifestation of a decrease in markers of endogenous intoxication, intermediate products of lipid peroxidation, correction of humoral and cellular immunity, activation of local immune reactions, hypocoagulation effect.
Keywords: ozone therapy; pathogenesis; oxidative stress; coagulogram; immunocorrection